Behavioral Foundations of Dividend Policy - Gholamreza Soleimani Amiri; Narges Goodarzi (مطالعات تجربی حسابداری مالی, 2012)
As the amount of dividend is one of the effective and final factors in investor decision making, dividend policy of companies that decides the amount of dividend, could play a very important role in making decisions. Dividend policy is reciprocally influenced by individual behavioral specifications. These specifications have an extensive coverage from which a few has been selected for this study. By measuring limits of patience and loss aversion of shareholders this study is trying to analyze their relations with companies’ dividend policy.The necessary data for trial assumptions, belonging to 77 companies for a period of 5 years between 1386-90, has been collected from Tehran stock exchange data base .the relation between variables have been examined by testing correlation coefficients and multiple regressions. Study shows there is no meaningful relation among percentage of dividend and stockholders patience, based on effecting date of dividend payment measurement and the amount of adjusted earnings per share measurement of companies accepted in Tehran stock exchange. On the other hand relation between dividend ratio percentage and measurement of companies profit growth is meaningful but to the contrary. So based on index of companies profit growth, a meaningful relation exists between payable dividend policy and loss aversion of shareholders. According to the market risk measurement, has no meaningful relation between loss aversion and dividend policy. Dividend Policy, Behavioral Finance, Patient Shareholders, Loss Averse Shareholders. Assistant